Consortia of Indigenous Rhizobacteria to Control Bacterial Wilt in Ginger - Naziha Diyanatur Rosiyah; Ayu Wike Widiasari; Achmad Roekhan; Restu Rizkyta Kusuma (Research Journal of Life Science, 2020)
Ginger (Zingiber officinale Rosc.) is a type of rhizome plant that has high potential to be developed in Indonesia as a medicinal plant or spice. Inhibiting factors in ginger production is Ralstonia solanacearum which causes bacterial wilt disease. Rhizobacteria is a potential biological agent to control the disease. It is necessary to review from various study on rhizobacteria both the use of antagonistic bacteria singly or in a consortia. Aimed to analyze various sources of scientific literature regarding the potential of antagonistic bacteria singly or consortia compared to synthetic bactericides in controlling of R. solanacearum. The results showed that three recommended antagonist bacteria were found, namely Pseudomonas fluorescens, Bacillus subtilis, and Bacillus thuringiensis. which has the potential to control bacterial wilt disease. The rhizobacterial consortia are more effective as a sustainable, safe and environmentally friendly control on bacterial wilt disease with a percentage of disease incidence 10%. In addition, the rhizobacterial consortia are three and six times more effective than the single antagonistic bacteria and bactericides respectively.